Globalization and Outbreak of COVID-19: An Empirical Analysis - Mohammad Reza Farzanegan; Mehdi Feizi; Hassan F. Gholipour (Center for Economic Studies and Ifo Institute (CESifo), 2020)
The purpose of this study is to examine the relationship between globalization, Coronavirus Disease 2019 (COVID-19) cases, and associated deaths in more than 100 countries. Our ordinary least squares multivariate regressions show that countries with higher levels of socio-economic globalization are exposed more to COVID-19 outbreak. Nevertheless, globalization cannot explain cross-country differences in COVID-19 confirmed deaths. The fatalities of coronavirus are mostly explained by cross-country variation in health infrastructures (e.g., share of out of pocket spending on health per capita and the number of hospital beds) and demographic structure (e.g., share of population beyond 65 years old in total population) of countries. Our least squares results are robust to controlling outliers and regional dummies. This finding provides the first empirical insight on the robust determinants of COVID-19 outbreak and its human costs across countries.
Keywords: I12; I18; I15; F63; F68; 330; COVID-19; globalization; public health